IMPLEMENTATION OF GREEN ECONOMY-BASED HUMAN RESOURCE TRAINING AND DEVELOPMENT IN SMALL AND MEDIUM INDUSTRIES IN BANJARMASIN CITY - Hasanah, Nurul; Yulianti, Farida (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The implementation of green economy-based training and human resource development in small and medium industries (SMEs) in Banjarmasin City is a strategic step in improving competitiveness and business sustainability. MSMEs in Banjarmasin show positive growth, but still face challenges in adopting environmentally friendly business practices. Therefore, training oriented towards energy efficiency, waste management, and the utilization of green raw materials is essential in supporting the transformation of the green economy. This research uses a literature study method with a literature research approach. The data used is secondary, including scientific journals, government reports, and academic publications that discuss the concept, policy, and implementation of the green economy in the MSME sector. The results show that green economy-based training contributes significantly to increasing the awareness and skills of SMEs in implementing sustainable business practices. This training also encourages the application of green technology, increases resource efficiency, and strengthens business competitiveness. Supporting factors for implementation include management awareness, government support, and collaboration with academics and the business community. However, there are several obstacles, such as limited knowledge, financial resources, and resistance to change and new technologies. In conclusion, the implementation of green economy-based HR training in SMEs in Banjarmasin City can improve competitiveness and business sustainability. The success of this program depends on government policy support, cross-sector collaboration, and continuous education for business actors.